In-depth analysis of crack area characteristics of fisheye failures influenced by the multiaxial stress condition in the tooth root fillet of high-strength gears. (May 2022) - Fuchs, Daniel; Rommel, Sascha; Tobie, Thomas; Stahl, Karsten
Modern high-strength gears have to satisfy many requirements, such as improved tooth root bending strength. The process of shot-peening is correlated to the introduction of compressive residual stresses in the surface layer of a gear to achieve a higher tooth root bending strength. However, due to the compressive residual stresses fisheye failures can occur and can have a determining effect on the endurance of high-strength gears. By preventing such failures, it should be possible to increase further the tooth root bending strength of high-strength gears. However, this requires a deeper understanding of the crack initiation and propagation processes. Especially the unique multiaxial stress condition in the tooth root fillet of a gear could influence the crack area characteristics significantly. Though, in the literature there is no proper characterization of crack area characteristics in the tooth root fillet of gears in detail, so far. Furthermore, in previous work a model approach for the evaluation of the tooth root bending strength of gears was presented, which is based on the results of Murakami. A first comparison with experimental data showed a basic applicability of the model approach on gears. However, the derived model approach showed some room for improvement. Questions arose as to whether the approach is really fully applicable to gears, whether further modifications are needed, or whether further extension is even practical, since the fisheye fracture characteristics of gears might differ significantly from those of standard specimens. The aim of this paper is therefore to present an extensive in-depth analysis of the crack area characteristics in the event of tooth root fracture damages caused by a fisheye failure in high-strength gears. Furthermore, a case study is used to verify whether a detailed evaluation of the characteristics of non-metallic inclusions leads to more accurate results of the model approach.